VARIASI HASIL TANGKAPAN IKAN DARI PERAIRAN SAMUDERA HINDIA, YANG DIDARATKAN DI PPN SIBOLGA PANTAI BARAT SUMATERA TAHUN 2019 - Manik, Ria R; Handoco, Ewin; Arleston, Jogi (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Overfishing and overcapacity is a problem for the sustainability of capture fisheries development. Indonesia has experienced overfishing or called overfishing and overcapacity or called excess fishing capacity. The west coast of the island of Sumatra has enormous fishing potential, both in territorial waters and in ZEE waters. The purpose of the study was to understand the trend of fluctuations in fish catches in the waters of West Sumatra. Assessing the effect of boat trips on fish catches in the waters of West Sumatra and providing basic information and management of fisheries in the waters of West Sumatra. The research material used is Catch per Unit Effort (CPUE) data. The overall data was monthly average data in 2019 with fishing ground areas in the Western waters of Sumatra, the Indian Ocean. The results showed the composition of catches in the waters of West Sumatra landed in PPN Sibolga there are three dominant types of fish, namely skipjack tuna 14.566.140 kg (49.90%), decapterus 6.404.470 kg (21.94%) and tunny 2.480.880 kg (8.50%), The dynamics of fish catches in PPN Sibolga in 2019 were highest in May at 3.945.143 kg and June was the lowest catch month of 1.093.292 kg and the average monthly catch in 2019 was 2.508.436 kg, the catch per business unit landed in PPN Sibolga in 2019 obtained the highest CPUE of 8.474 kg/trip (July 2019) and the lowest 1,755 kg/trip (June 2019). ABSTRAK Overfishing dan overcapacity erupakan masalah keberlanjutan pembangunan perikanan tangkap. Indonesialah mengalami overfishing atau disebut penangkapan berlebih dan overcapacity atau disebut kelebihan kapasitas penangkapan. Pantai Barat Pulau Sumatera memiliki potensi perikanan yang sangat besar, baik perairan teritorial maupun perairan ZEE. Tujuan dari penelitian adalah untuk memahami trend fluktuasi hasil tangkapan ikan di Perairan Barat Sumatera, mengkaji pengaruh trip kapal dengan hasil tangkapan ikan di Perairan Barat Sumatera dan memberikan informasi dasar dan pengelolaan perikanan di Perairan Barat Sumatera. Materi penelitian yang digunakan adalah data Catch per Unit Effort (CPUE). Keseluruhan data merupakan data rata-rata bulanan tahun 2019 dengan daerah fishing ground Perairan Barat Sumatera Samudera Hindia. Hasil penelitian menunjukkan komposisi hasil tangkapan di Perairan Barat Sumatera yang didaratkan di PPN Sibolga terdapat tiga jenis ikan yang dominan yaitu cakalang 14.566.140 kg (49,90%), layang 404.470 kg (21,94%) dan tongkol 2.480.880 kg (8,50%), Dinamika hasil tangkapan ikan di PPN Sibolga di tahun 2019 tertinggi terjadi pada bulan Mei sebesar 3.945.143 kg dan bulan Juni merupakan bulan hasil tangkapan terendah yaitu 1.093.292 kg dan rata-rata hasil tangkapan bulanan tahun 2019 adalah 2.508.436 kg, Hasil tangkapan per-unit usaha yang didaratkan di PPN Sibolga di tahun 2019 didapatkan CPUE tertinggi yaitu 8.474 kg/trip (Juli 2019) dan terendah 1.755 kg/trip (Juni 2019). Kata Kunci: CPUE, penangkapan berlebih, penangkapan ikan, PPN Sibolga, Perairan Barat Sumatera